1972
DOI: 10.1177/07067437720176s232
|View full text |Cite
|
Sign up to set email alerts
|

Dreams and Demography

Abstract: tSignifiCant differences reported are all based upon X• tests with probability levels appropriate to the degrees of freedom. Tables of normative data for all demographic variables and content scales are available upon request.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
35
4

Year Published

1994
1994
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 36 publications
7
35
4
Order By: Relevance
“…The frequencies in our population study [51] are similar to what Hall and Van de Castle [9] reported from their study of college age dreamers. The differences from Hall-Van de Castle may be attributable to the population study having shorter dreams and a wider age range.…”
Section: Introductionsupporting
confidence: 90%
See 4 more Smart Citations
“…The frequencies in our population study [51] are similar to what Hall and Van de Castle [9] reported from their study of college age dreamers. The differences from Hall-Van de Castle may be attributable to the population study having shorter dreams and a wider age range.…”
Section: Introductionsupporting
confidence: 90%
“…The major organizer of dream content is the sex of the dreamer. We found [51] very few dream content differences related to the race or marital status of the dreamer.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations